Development of a terawatt coherent white light lidar system and applications to environmental studies - Yamanaka, Chihiro (Animo Repository, 2008)
We have been developing a coherent "white light" lidar using a terawatt laser system at 800 nm with a 9m length krypton gas cell, which emits a coherent supercontinuum from UV to near infrared regions. Linearly polarized supercontinuum was transmitted to the atmosphere, and backscattered light was collected with a telescope of 31.8 cm in a diameter and the light was separated into 3 to 5 wavelengths using dichroic mirrors and interference filters. Mainly, we used the wavelengths of 450, 550, 700nm and 800 nm with each bandwidth of 10 to 40 nm. Although, the energy of light included in each wavelength range is restricted, the advantage of multi-spectral features on the same optical axis of this system enables us to use preferred spectral lines for various measurements. The system was successfully applied as a depolarization lidar as well as a multi line Mie scattering lidar for cloud particles and Aeolian dusts. By comparing the response for each spectrum, we can determine the size of particles with information on their shapes. Current research is focused to find applications in near infrared region of the white light. © 2008 SPIE.